PREVENTION OF RECIDIVISM - THEORETICAL REFERENCES - PREDA, Aura – Marcela (International Journal of Legal and Social Order, 2022)
Regardless of the model, forms and/or strategies of crime prevention, we believe that a component related to the prevention of recidivism should not be missing. Through this article, we aim to highlight some theoretical aspects that could be taken into account in the foundation of some public/penal policies in our country, starting with conceptual clarifications, pointing out prevention models and representative theories and ending with some conclusions.